2017
DOI: 10.1002/slct.201700229
|View full text |Cite
|
Sign up to set email alerts
|

A Green Access to Tetrahydro-1H-pyrano[2,3-d]pyrimidines: Visible-Light-Triggered and Ethylene-Glycol-Mediated Multicomponent One-Pot Process.

Abstract: Efficient and environmentally benign heterocyclization via Knoevenagel condensation followed by [4 + 2] cycloaddition resulting the synthesis of tetrahydro-1H-pyrano[2,3-d]pyrimidine derivatives starting from 2-thiobarbutiric acid, aldehydes and alkyne has been reported. Easily available ethylene glycol was used as a green promoting medium as well as solvent for the reaction progress. This methodology offers a metal and base free approach which endowed high yields with mild reaction conditions and better funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…Moreover, it has been found that in different types of tumor cells, neuropilins (NRPs) such as NRP2 facilitate tumor metastasis 30,31 . Increased expression of NRP2 leads to an elevated rate of cell proliferation in melanoma cells and enhances cell metastasis 32–38 . In the present study, invasive potential of Kyse‐270 and EC9706 cells showed a pronounced decrease on incubation with TDFPT compared with the control cultures.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Moreover, it has been found that in different types of tumor cells, neuropilins (NRPs) such as NRP2 facilitate tumor metastasis 30,31 . Increased expression of NRP2 leads to an elevated rate of cell proliferation in melanoma cells and enhances cell metastasis 32–38 . In the present study, invasive potential of Kyse‐270 and EC9706 cells showed a pronounced decrease on incubation with TDFPT compared with the control cultures.…”
Section: Discussionsupporting
confidence: 46%
“…30,31 Increased expression of NRP2 leads to an elevated rate of cell proliferation in melanoma cells and enhances cell metastasis. [32][33][34][35][36][37][38] In the present study, invasive…”
Section: Discussionmentioning
confidence: 95%
“…Researchers have effectively explored the visible lightmediated synthesis of pyrano[2,3-d]pyrimidine compounds. Ibad et al (2017) used ethylene glycol as a green solvent and promoter to synthesize tetrahydro-1H-pyrano[2,3-d] pyrimidine derivatives, achieving high yields under mild conditions. Mohamadpour developed a green method for making pyrano[2,3-d] pyrimidine scaffolds using visible light irradiation to promote Knoevenagel-Michael cyclocondensation without a catalyst or solvent.…”
Section: Visible Light-mediated Synthesis Of Pyrano[23d]pyrimidine Co...mentioning
confidence: 99%
“…Using ethylene glycol as a green solvent and promoter, Ibad et al [77] synthesized tetrahydro-1H-pyrano[2,3-d] pyrimidine 60 derivatives in 2017 by performing Knoevenagel condensation and [4 + 2] cycloaddition. The method was metal-free and base-free and achieved high yields under mild conditions with good functional group compatibility.…”
Section: Visible Light-mediated Synthesis Of Pyrano[23d]pyrimidine Co...mentioning
confidence: 99%
“…Ibad et al 161 reported a novel and green synthetic route to afford tetrahydro-1 H -pyrano[2,3- d ]-pyrimidine 123 by heterocyclization through Knoevenagel condensation of 2-thiobarbituric acid 11a (2 mmol) and 1 (2 mmol) to form cyclic adduct 5-arylidine thiobarbituric acid which then undergo [4+2] cycloaddition with internal alkynes’ derivatives 83 / 83b / 83c / 83d / 83e (2 mmol) in the presence of ethylene glycol acting as a catalyst as well as solvent under visible blue-LED light irradiation (24 W) ( Scheme 86 ). 1 carrying electron-releasing substituents gave higher yields of 123 in lower reaction time than those carrying electron-withdrawing substituents and also symmetrical alkynes produced a higher yield of the product than asymmetrical alkynes.…”
Section: Synthesis Of 5-aryl-substituted Pyrano[23- D ...mentioning
confidence: 99%